Minoan realities: approaches to images, architecture, and society in the Aegean Bronze Age - Panagiotopoulos, Diamantis; Günkel-Maschek, Ute (Aegis, 2012)
What is the social role of images and architecture in a pre-modern society? How were they used to create adequate environments for specific profane and ritual activities? In which ways did they interact with each other? These and other crucial issues on the social significance of imagery and built structures in Neopalatial Crete were the subject of a workshop which took place on November 16th, 2009 at the University of Heidelberg. The papers presented in the workshop are collected in the present volume. They provide different approaches to this complex topic and are aimed at a better understanding of the formation, role, and perception of images and architecture in a very dynamic social landscape. The Cretan Neopalatial period saw a rapid increase in the number of palaces and 'villas', characterized by elaborate designs and idiosyncratic architectural patterns which were themselves in turn generated by a pressing desire for a distinctive social and performative environment
ISBN falsch im Buch
Keywords: Konferenzschrift -- 2009 -- Heidelberg; Aufsatzsammlung; Architektur; Minoische Kultur